An affinity-directed phosphatase, AdPhosphatase, system for targeted protein dephosphorylation. Issue 2 (16th February 2023) - Simpson, Luke M.; Fulcher, Luke J.; Sathe, Gajanan; Brewer, Abigail; Zhao, Jin-Feng; Squair, Daniel R.; Crooks, Jennifer; Wightman, Melanie; Wood, Nicola T.; Gourlay, Robert; Varghese, Joby; Soares, Renata F.; et al.
Summary: Reversible protein phosphorylation, catalyzed by protein kinases and phosphatases, is a fundamental process that controls protein function and intracellular signaling. Failure of phospho-control accounts for many human diseases. While a kinase phosphorylates multiple substrates, a substrate is often phosphorylated by multiple kinases. This renders phospho-control at the substrate level challenging, as it requires inhibition of multiple kinases, which would thus affect other kinase substrates. Here, we describe the development and application of the affinity-directed phosphatase (AdPhosphatase) system for targeted dephosphorylation of specific phospho-substrates. By deploying the Protein Phosphatase 1 or 2A catalytic subunits conjugated to an antigen-stabilized anti-GFP nanobody, we can promote the dephosphorylation of two independent phospho-proteins, FAM83D or ULK1, knocked in with GFP-tags using CRISPR-Cas9, with exquisite specificity. By redirecting protein phosphatases to neo-substrates through nanobody-mediated proximity, AdPhosphatase can alter the phospho-status and function of target proteins and thus, offers a new modality for potential drug discovery approaches. Graphical abstract: Highlights: Affinity-directed phosphatase (AdPhosphatase) can mediate protein dephosphorylation AdPhosphatase consists of a target binder conjugated to a phosphatase catalytic subunit Target dephosphorylation by AdPhosphatase requires phosphatase catalytic activity AdPhosphatase system can be used to study the role of target protein phosphorylation Abstract : Simpson and Fulcher et al. describe the development of an affinity-directed phosphatase (AdPhosphatase) system to promote targeted dephosphorylation of phosphorylated proteins of interest (POIs). The AdPhosphatase consists of a POI-binding nanobody conjugated to the catalytic subunit of a promiscuous phosphatase (PPP1CA/PPP2CA), which can mediate POI dephosphorylation through proximity in cells.